Semantic Enterprise Architecture Oriented Test Case Generation for Business process - M. Rahmanian; R. Nassiri; M. Mohsenzadeh; R. Ravanmehr (Journal of Electrical and Computer Engineering Innovations, 2022)
Background and Objectives: The area of enterprise architecture encompasses various domains, the most complicated of which concerns developing an enterprise business architecture. Although many state-of-the-art enterprise architecture frameworks describe the architecture by abstract levels, they still fail to provide accurate syntactic and semantic descriptions. Several previous conducted studies were looking for different objectives elaborated on modeling enterprise architectures. However, none of those studies tried to develop a modeling that generates test cases which would later be used for validation and/or verification. Therefore, the main contribution of this study is generating a set of test cases based on the descriptions yielded from enterprise business processes in early steps; then, the amount of later reviews and changes can be significantly lessened.Methods: Following the objective of accurate validation and/or verification of the enterprise business processes within an enterprise's architecture development, this paper proposes a new method based on the enterprise architecture design. Throughout the iterative cycle of the proposed method, initially, the enterprise goals will be extracted based on the TOGAF framework. Afterwards, it will be subjected to syntactical modeling based on the Archimate language. Then, semantics will be added to the syntactic model of the enterprise business processes based on the WSMO framework and formalize manually to B language by using defined transition rule. Therefore, in order to discover test cases, a set of test coverage will be tested on the formal model. Results: The proposed method has been implemented in the marketing and sales department of a petrochemical corporation, where the results show the validity and also the effectiveness of the method. Based on the implementation of our method on the selected case study, the details of the business process have been defined based on an enterprise level, the level of abstraction is decreased by syntactic and semantic modeling of enterprise architecture description, the formal descriptions created using the proposed transition rules for sampling.Conclusion: The proposed method starts from the goals of enterprises; therefore, the output samples are efficiently precise. By adding semantics to the syntactic models of enterprise architecture, the degree of abstraction has been decreased. By creating a formal model, the model can be subjected to sampling. For future work, it is suggested to use the proposed method for the automatic generation of codes.